Espinoza, G. Antonio. Education and the State in Modern Peru: Primary Schooling in Lima, 1821 - c. 1921. Nueva York: Palgrave Macmillan, 2013, 283 pp. - Peralta Cruz, Víctor (2015)
No presenta resumen